An Adaptive Vertical Handoff Algorithm Based on UMTS and WLAN - Jin Ling; Zhang Hui; Yang Long-Xiang; Zhu Hong-Bo (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
According to the characteristics of heterogeneous networks and user demand for seamlessly connection, the necessity of handoff to WLAN was researched.  First of all, in order to reduce the influence of shadow fading on received signal strength (RSS), a smoothing algorithm based on support functions was proposed. Then, considering the context of mobile terminals and networks, and by using probabilistic knowledge, we propose an adaptive vertical handoff algorithm based on compensating time. The simulation results show that, compared with two algorithms, the proposed algorithm can make more effective and accurate handoff decisions, reduce the ping-pong effect and interruption probability, thereby greatly improving handoff performance. DOI : http://dx.doi.org/10.11591/telkomnika.v12i5.4276